Collaborative monitoring of production and costs of timber harvest operations in the Brazilian Amazon - Pokorny, B.; Steinbrenner, M. (2005)
Timber companies and policy makers in the Brazilian Amazon urgently need financial information on forest management. Results from a few experiments, case studies, and surveys have been groundbreaking, but are insufficient. A strategic partnership between timber companies and research organizations is needed to generate additional information. This paper presents a tool for monitoring production and costs of forest operations to facilitate such collaboration. The tool provides useful information for companies and, at the same time, generates reliable data for research. Selected results are presented on production, capacity, and costs to demonstrate the usefulness of the information that can be generated. These results are based on the first 2 years of implementation by a company in the State of Pará, Brazil. This pilot project confirmed that the tool is simple and relevant. Its successful implementation requires significant investment, and will be applicable only to companies interested in changing from conventional logging to reduced-impact logging, especially those seeking Forest Stewardship Council certification. Successful implementation of the tool will also depend on it generating readily understood and highly relevant results for the companies, and receiving extensive support during the first 2 years.